Can cyst volume be used to stratify risk of complications following cyst defect reconstruction with iliac crest graft?. Issue 8 (August 2017) - Safi, Ali-Farid; Grandoch, Andrea; Dreiseidler, Timo; Nickenig, Hans-Joachim; Zöller, Joachim; Kreppel, Matthias
Abstract: Introduction: The role of the volume of radicular and dentigerous cysts on clinical symptoms is unclear and potentially may predict development of pre- and postoperative complications, especially after cystectomies with large bony defects. Therefore the aim of this study was to assess pre- and postoperative symptoms associated to the volume of jaw cysts. Material and methods: Retrospective chart review of 111 patients with follicular or dentigerous cysts from 2008–2012. Anterior iliac crest grafts were used to fill defects after cystectomy. χ 2 -test was performed to analyze associations between two qualitative variables. Binary logistic regression analysis was used as multivariate analysis. P-values p < 0.05 were considered as significant. Volume measurement was performed in a semiautomatic segmentation method with the software "ITK-Snap". Results: Postoperative hypaesthesia correlated significantly with histology (p = 0.025) and localization (p = 0.006). Volume was associated significantly with preoperative hypaesthesia (p = 0.052), postoperative hypaesthesia (p < 0.001), wound healing complications (p < 0.001) and length of wound healing complications (p = 0.001). Multivariate analysis identified volume as independent risk factor for postoperative hypaesthesia (p = 0.015). Conclusions: Volume analysis appears to be a method that allows risk stratification after surgery of jaw cysts. Therefore we recommend a precise treatment planning with the means of volume analysis to improve therapy outcome of patients with jaw cysts.